Anti-diabetic medication burden amongst older persons with diabetes and associated quality of life - Shalihin, Mohd Shaiful Ehsan; Fauzi, Abdullah; Zulkifli, Nurul Afiqah; Abdul Aziz, Azrul Aziz (Malaysian Medical Association, 2020)
Background: Older persons with diabetes are the major demographic of diabetic patients followed up in primary health clinics. Despite their increasing age and morbidities, They are still being managed strictly towards good sugar control in order to achieve the ideal HbA1c level without taking their quality of life into consideration. This study aimed to determine the prevalence in the use of antidiabetic drugs among older persons with diabetes and its association with their quality of life. Methodology: A cross-sectional study was conducted among 269 older persons with diabetes in all government health clinics in Kuantan using Diabetes Quality of Life questionnaire. SPSS version 23 was used for the statistical analysis. Results: Majority of the respondents were females (61%), Malays (84.8%), pensioners (54.3%) with education up to primary school (52%) and are staying with family members (93.7%). Most of the patients were on two antidiabetic agents (48%) followed by a single antidiabetic agent (32%). Despite the risk of hypoglycaemia, 0.4% of them are on glibenclamide. The use of insulin is still common among 21% of them that are on intermediate-acting insulin, 15.6% on premixed insulin and 7.8% on short-acting insulin. Those taking a higher number of antidiabetic agents were found to be associated with poorer quality of life (p=0.001) compared to those taking one or two antidiabetic medications. Those on insulin also have significantly poorer quality of life score (p=0.012). Conclusion: Despite aiming for controlled diabetes, older persons suffer poor quality of life with further intensification of their antidiabetic medications according to the guidelines. This includes the complexity of insulin usage and polypharmacy, which contribute to the low quality of life score.